The influence of human values on the consumption of Seco Encerado cheese from the Istmo of Tehuantepec, Oaxaca, and its meanings: the mediating effect of tangible attributes - Martínez Aquino, Valeria; Hernández Montes, Arturo; Hernández Rodríguez, Blanca Elizabeth; Santos Moreno, Armando (Acta Universitaria, 2023)
The purpose was to identify the routes of influence of human values on the consumption of Seco Encerado cheese and the communalities of its meanings. A questionnaire was administered to 202 consumers, who assessed the importance of 40 human values and 11 tangible attributes (independent variables) as well as the frequency of consumption (dependent variable). After showing a picture of the cheese to the consumers, three of their ideas about it were recorded. Three multiple linear regressions were performed with the factors obtained from the factor analysis: (B1) consumption and tangible attributes; (B2) consumption and human values, plus residuals of tangible attributes; and (B3) consumption with human values. Direct influence (B2R2 - B1R1) and indirect influence (∆R - B3R3) were calculated. For the meanings, the K-proportions test was applied. The route of influence of human values was indirect, while symbolic and utilitarian psychological meanings were statistically equal.